Optimization of the Process of Producing Porcelain Stoneware from Mineral Raw Materials and Microsilica as a Secondary Raw Material; Ceramics; Vol. 8, iss. 4 - Darkhan A. Assel; Anarbayev A. Abibulla; Yessimov B. O. Begen Omarovich; Vakalova T. V. Tatyana Viktorovna; Stanevich V. Victor; Molodykh A. Alina (2025, 2025)
Title screen